Meta model construction mechanism in SDN architecture - Bin ZHUGE; Hua ZHU; Baoxia WANG; Weiming WANG; Julong LAN (Dianxin kexue)
Micro service is a new method of modern application architecture,its characteristic is that decomposing the complex applications into discrete,independent service,so that decoupling of applications scheme can be achieved,and the individual service could be developed,deployed and extensioned independently.The change of the application must drive on the change of the underlying network,the architecture of reconfigurable fundamental information communication network aimd to compensate for the network business requirements and network transmission capacity through the network reconfiguration mechanism.A meta model construction mechanism with the SDN architecture for fusion the reconfiguration and software defined network technology was proposed,it aimed to present the services of each layer in the SDN architecture by the form of meta model.And after referencing the AKF scale cube,a kind of meta model building method based on orthogonal decomposition was proposed.Finally,the feasibility of meta model building method based on orthogonal decomposition from the theoretical analysis and development of example was verified.